A New Frontier in Ionospheric Observations: GPS Total Electron Content Measurements From Ocean Buoys. Issue 11 (9th November 2020) - Azeem, Irfan; Crowley, Geoff; Forsythe, Victoriya V.; Reynolds, Adam S.; Stromberg, Erik M.; Wilson, Gordon R.; Kohler, Craig A.
Abstract: Ground‐based Global Navigation Satellite System (GNSS) receivers have become a ubiquitous tool for monitoring the ionosphere. Total electron content (TEC) data from globally distributed networks of ground‐based GNSS receivers are increasingly being used to characterize the ionosphere and its variability. The deployment of these GNSS receivers is currently limited to landmasses. This means that 7/10 of Earth's surface, which is covered by the oceans, is left unexplored for persistent ionospheric measurements. In this paper, we describe a new low‐power dual‐frequency Global Positioning System (GPS) receiver, called Remote Ionospheric Observatory (RIO), which is capable of operating from locations in the air, space, and the oceans as well as on land. Two RIO receivers were deployed and operated from the Tropical Atmosphere Ocean buoys in the Pacific Ocean, and the results are described in this paper. This is the first time that GPS receivers have been operated in open waters for an extended period. Data collected between 1 September 2018 and 31 December 2019 are shown. The observed TEC exhibits a clear seasonal dependence characterized by equinoctial maxima in the data at both locations. Both RIO receivers, deployed near the magnetic equator, show an 18–35% increase in TEC during moderately disturbed geomagnetic periods. Comparisons with the International Reference Ionosphere model show good agreement. The new capability presented in this paper addresses a critical gap in our ability to monitor the ionosphere from the 70% of the Earth's surface that is covered by water. Plain Language Summary: The upper levels of the atmosphere, from about 80 to over 1, 000 km altitudes, collectively referred to as the ionosphere, consist of partially ionized gas. An increasingly large amount of ionospheric data comes from ground‐based receivers that passively benefit from the signals transmitted on board the Global Navigation Satellite System (GNSS) constellations. One of the most useful data sets provided by these GNSS receivers is the total electron content. Ground‐based GNSS receivers are widely deployed all over the world and have become the workhorse for doing ionospheric research. However, to date, the deployment of these GNSS receivers has been limited to landmasses, which leaves 70% of the Earth's surface covered by the oceans uninstrumented for ionospheric studies. In this paper, we describe a new low‐power dual‐frequency Global Positioning System receiver, called the Remote Ionospheric Observatory, which is capable of continuous operation from ocean buoys for extended periods. We present data from two Remote Ionospheric Observatory receivers deployed on buoys in the Pacific Ocean. The new capability described in this paper is anticipated to open up many new applications for passively monitoring the ionosphere from previously inaccessible regions, such as the ocean. Key Points: A new capability for measuring total electron content (TEC) from the ocean surface is presented First measurements of TEC from two surface buoys in the Pacific Ocean are described TEC enhancements in the equatorial region during moderate geomagnetic storms are observed